Long-Term Vibration Monitoring of the Effects of Temperature and Humidity on PC Girders with and without Fly Ash considering ASR Deterioration - Tuan Minh Ha; Saiji Fukada; Kazuyuki Torii (Shock and Vibration)
Structural responses have been used as inputs in the evaluation procedures of civil structures for years. Apart from the degradation of a structure itself, changes in the environmental conditions affect its characteristics. For adequate maintenance, it is necessary to quantify the environment-induced changes and discriminate them from the effects due to damage. This study investigates the variation in the vibration responses of prestressed concrete (PC) girders, which were deteriorated because of the alkali–silica reaction (ASR), concerning ambient temperature and humidity. Three PC girders were exposed to outdoor weather conditions outside the laboratory, one of which had a selected amount of fly ash in its mixture to mitigate the ASR. The girders were periodically vibration tested for one and a half years. It was found that when the temperature and humidity increased, the frequencies and damping ratios decreased in proportion. No apparent variation in the mode shapes could be identified. A finite element model was proposed for numerical verification, the results of which were in good agreement with the measured changes in the natural frequencies. Moreover, the different dynamic performances of the three specimens indicated that the fly ash significantly affected the vibrations of the PC girders under ASR deterioration.